Polarization dependence of the light coupling to surface plasmons in an Ag nanoparticle ＆ Ag nanowire system - 杨超杰 赵华波 王培培 李洁 唐鹏 曲胜春 林峰 朱星 (Chinese physics B, 2014)
Polarization dependence of the coupling of excitation light to surface plasmon polaritons （SPPs） was investigated in a Ag nanoparticle-nanowire waveguide system （a Ag nanoparticle attached to a Ag nanowire）. It was found that under the illumination of excitation light on the nanoparticle-nanowire junction, the coupling efficiency of light to SPPs depends on the polarization of the excitation light. Theoretical simulations revealed that it is the local near-field coupling between the nanoparticle and the nanowire that enhances the incident light to excite the nanowire SPPs. Because the shapes of the Ag nanoparticles differ, the local field intensity, and thus the excitement of the nanowire SPPs, vary with the polarization of the excitation light.